Stealthy Invader: Cryptosporidium’s Unseen Prevalence in Western Maharashtra - Patel, Amit; Sing, Neha; Paul, Abhishek; Patil, Sunita Desairao; Khobragade, Komal Prakash (Annals of Pathology and Laboratory Medicine, 2024)
Background: In developing countries, enteric parasitic protozoa of the genus Cryptosporidium have emerged as a major source of diarrhoea. They can cause both acute and chronic diarrhoea in immune-compromised as well as immunocompetent individuals. The purpose of this study was to ascertain the prevalence of Cryptosporidium spp. as an enteric pathogen responsible for diarrhoea in immunocompetent individuals. Objective: To estimate the prevalence of Cryptosporidium infection among immunocompetent individuals suffering from gastrointestinal (GI) symptoms. Materials and Methods: A cross-sectional study was conducted at the Microbiology Laboratory of a tertiary care hospital in Western Maharashtra from March 2022 to February 2023. Stool specimens from patients presenting with GI symptoms were collected. To identify Cryptosporidium oocysts, direct stool smears were prepared, air-dried, and stained using a modified Kinyoun’s acid-fast technique. Oval and round acid-fast bodies (dark pink), 4-5 μm in size, were identified as Cryptosporidium oocysts after being examined by two observers. Results: A total of 132 samples were included in this study, of which 110 (83.3%) tested positive for Cryptosporidium oocysts. The study found a high prevalence (83.3%) of Cryptosporidium spp. in immunocompetent patients with GI symptoms. Conclusion: The significant prevalence identified in this study underscores the necessity of routine screening for Cryptosporidium parasites as part of diagnostic protocols for patients presenting with GI symptoms.